2008
DOI: 10.3399/bjgp08x376195
|View full text |Cite
|
Sign up to set email alerts
|

Trends and inequities in beta-blocker prescribing for heart failure

Abstract: Treatment with specific beta-blockers reduces mortality and hospitalisation in heart failure. AimTo describe trends and inequities in beta-blocker prescribing for heart failure. Design of studyRepeated cross-sectional analysis of a nationally representative primary care database (DIN-LINK). SettingA total of 152 UK general practices. MethodPrescribing of beta-blockers between 2000 and 2005 was examined among a yearly average of 7294 patients aged ≥50 years who had actively managed heart failure -defined as a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 29 publications
2
47
0
Order By: Relevance
“…A more recent study observed underuse of ␤-blockers among patients living in the most deprived areas of the United Kingdom. 6 The extent to which any healthcare system in the world is delivering equitable HF care is thus uncertain.…”
Section: Editorial See P 1006 Clinical Perspective On P 1057mentioning
confidence: 99%
See 2 more Smart Citations
“…A more recent study observed underuse of ␤-blockers among patients living in the most deprived areas of the United Kingdom. 6 The extent to which any healthcare system in the world is delivering equitable HF care is thus uncertain.…”
Section: Editorial See P 1006 Clinical Perspective On P 1057mentioning
confidence: 99%
“…2,6,7,9 The US National Heart Failure Project constructed a nationally representative cohort of elderly Medicare beneficiaries by randomly sampling hospitalizations from each state between 1998 and 1999. 2 Adjusted likelihood of ACEI prescription at discharge was similar in patients of lower and higher socioeconomic status (RR, 1.03; 95% CI, 0.93-1.11).…”
Section: Treatment: Socioeconomic Inequalitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, a number of studies from Europe have found consistently lower use of ACE-inhibitors and beta blockers in older outpatients, although many of these studies have methodologic limitations and had limited ability to account for potential confounders. 13,[34][35][36] Our results suggest that interpreting age differences in prescribing requires nuance. In our study, older patients had meaningfully lower rates of ACE inhibitor/ARB and beta blocker use in both absolute and relative terms, and the frequency of chart-documented reasons for not prescribing these drugs did not vary between age groups.…”
Section: Discussionmentioning
confidence: 99%
“…1 We recently investigated use of home blood pressure (BP) monitoring in stroke patients registered at a deprived inner city general practice in Lambeth. In March 2008 we sent confidential postal questionnaires, backed up by a telephone call if required, to 74 patients listed on the stroke register at an inner London general practice.…”
mentioning
confidence: 99%